ISLAMIC ARCHITECTURE APPROACH IN MUSLIMAH SPORTS CENTRE’S LAYOUT - Fahira Fahira; Dian Pramita Eka Laksmiyanti; Firdha Ayu Atika (Journal of Civil Engineering, Planning and Design, 2022)
Muslimah or women who believe in Islam have various kinds of etiquette restrictions when leaving the house. One of them is etiquette in doing sports. Sports that require active movement, have made it difficult for Muslimah to find public facilities that can accommodate sports without violating Islamic law. According to data, Tambaksari District is a geographically strategic place with the largest Muslim population in Surabaya. This potential supports the existence of the Muslimah Sports Centre in Tambaksari. So that Muslim women will get a sports place that is strategic, comfortable, and safe without male intervention. With mixed research between quantitative and qualitative method, this quantitative research assumes an objective reality and a view of the researcher as independent of the subject of inquiry, while qualitative research involved the study of the use and collection of various empirical materials, which eventually presented the perspective of Muslimah’s experiences. The Muslimah Sports Centre has a big goal of creating a better cultural system for religious behavior by understanding things that have been explained in the Al-Quran and As-Sunnah. Thus, the building will serve not only as a means of sports activities but also as a place for providing Islamic values to the users of the building. For this reason, the design of the Muslimah Sports Centre applies an Islamic architectural approach. Because the aim of this study is to provide an understanding that architecture not only serves as a basic reference for developing buildings and their architectural elements, but it can also provide an understanding and learning about how to behave in accordance with the Qur'an and Sunnah inside the building so that we will not violate Islamic law.